Replication Data for: Assessment of Napier grass accessions in lowland and highland tropical environments in east Africa: productivity and forage quality - Mwendia, Solomon W.; Yunusa, Isa; Sindel, Brian; Whalley, Ralph; Kariuki, Innocent (International Center for Tropical Agriculture, 2016)
This was a trial on evaluating Napier grass cultivars performance under two contrasting environments (lowlands and highlands) in Kenya.